2013
DOI: 10.4103/0378-6323.104667
|View full text |Cite
|
Sign up to set email alerts
|

Upper face rejuvenation using botulinum toxin and hyaluronic acid fillers

Abstract: The demand for facial rejuvenation is increasing, with each passing day, in all age groups. A number of procedures like chemical peels, microdermabrasion, laser and light therapies, and minimally invasive procedures like botulinum toxin injections (BTX A) and hyaluronic acid (HA) fillers are being extensively used by the dermatologist and plastic surgeons to meet this growing demand. A good knowledge of use of these techniques is becoming imperative for the dermatologist. In the present article, we discuss in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…However, the botulinum toxin dosage required to treat upper static forehead lines is higher in men than women (Table 4 ), in agreement with other findings in Indians. 21 , 22 , 33…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the botulinum toxin dosage required to treat upper static forehead lines is higher in men than women (Table 4 ), in agreement with other findings in Indians. 21 , 22 , 33…”
Section: Resultsmentioning
confidence: 99%
“…Indian women prefer a high arched brow, with no lateral flare 21 ; hence, for a brow lift with an arch, the medial frontalis is treated in addition to the brow depressors to achieve the desired eyebrow shape.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of fillers for soft tissue augmentation has also brought into focus a simplified nonsurgical technique for rejuvenating the upper face, with minimal downtime. The article by Nanda and Bansal [2] published in this issue highlights the finer nuances of both these techniques for rejuvenation of the upper face as well as complications that can occur. The authors have detailed the procedures and rightly concluded that a thorough knowledge of the basic anatomy, proper patient selection and following proper guidelines makesthese procedures safe and effective for rejuvenation.…”
mentioning
confidence: 96%